PERAN DAKWAH MELALUI BIMBINGAN DAN KONSELING DALAM MEMBINA KEHARMONISAN RUMAH TANGGA - Suriati, Suriati (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 9 No 1 (2013), 2013)
Da'wah has  many  forms. One  of them  is guidance  and counseling. but da'wah in the form of guidance and counseling is still not so often performed. Preachers  more oriented preaching in the pulpit or on takllm assemblies. Though  not  all people  problem  be  missed through  such forms of da 'wah.  Guidance and counseling is one of the techniques in solving people's problems, especially problems of households. Through  guidance and  counseling, domestic harmony can be  achieved by every Muslim family. guidance and counseling should try and take on the role to foster harmony in the household, including the development of a state trying to do a better direction, healing, repair, and maintenance of household Islam by using approaches  and techniques in guidance and counseling.